Methodological guidelines for performing practical work in the academic discipline: "Mathematical models of composite materials" in the section "Mathematical modeling of elastic and strength properties of composites and laminates" - Fedorov, V. O. (Національний технічний університет "Харківський політехнічний інститут", 2026)
The relevance of acquiring knowledge and skills in mathematical models of composite materials stems from practical and theoretical factors, the main of which are the high quality and wide application of such materials in all areas of life, as well as the specificity of their mathematical models compared to traditional materials. Individual tasks are performed with the aim of consolidating theoretical knowledge and acquiring practical skills in calculating the elastic and strength properties of composites and laminates. All tasks are performed according to options. To complete the work, you should know the basics of the theory of elasticity and master the relevant sections of the theory of strength. The work is done in a separate notebook and is defended within two weeks from the moment of receiving the assignment. The defense involves answering control questions and commenting on calculations and results. The assessment is carried out according to the following main parameters: - knowledge of theoretical principles; - correctness and completeness of decisions and comments to it; - timeliness of preparation; - accuracy of the report. To complete the tasks and prepare the report, knowledge of the following issues is required.
Keywords: methodological guidelines; practical work; mathematical models; composite materials; composites; laminates